Combined Anterior Cruciate Ligament and Anterolateral Ligament Reconstruction Results in Superior Rotational Stability Compared with Isolated Anterior Cruciate Ligament Reconstruction in High Grade Pivoting Sport Patients: A Prospective Randomized Clinical Trial - Mogoş, Ştefan; D'Ambrosi, Riccardo; Antonescu, Dinu; Stoica, Ioan-Cristian (The Journal of Knee Surgery, 2021)
The purpose of the current randomized clinical trial (RCT) was to evaluate the clinical outcomes of combined anterior cruciate ligament (ACL) and anterolateral ligament (ALL) reconstruction and to compare them with those of isolated ACL reconstruction. The hypothesis was that combined ACL and ALL reconstruction will result in superior clinical outcomes in terms of the rotational stability of the knee. This prospective RCT included 57 patients (44 men and 13 women, mean age = 31 ± 7.1 years) who underwent ACL reconstruction either isolated (Group I: 25 patients) or combined with ALL reconstruction (Group II: 32 patients). The evaluation of the patients was done preoperatively and postoperatively at 6 weeks, 12 weeks, 6 months, and 12 months including a clinical examination (Lachman's test, Pivot shift's test, and Rolimeter differential anterior laxity), an objective clinical scores (objective: the International Knee Documentation Committee [IKDC] score) and a subjective clinical scores (subjective: IKDC's score, Lysholm's score, and Tegner's activity score). Postoperative complications of all the patients were recorded. There was a significant difference between the study groups at all follow-up intervals when evaluating the postoperative pivot shift test (p < 0.05) with a superior rotational stability in the group of combined ACL and ALL reconstruction. At the final follow-up evaluation, 36% of the patients from Group I and 6.2% in Group II had a grade I positive pivot shift test (p < 0.05). There was a statistically significant difference between the two groups regarding the number of patients with a grade A IKDC objective score (p < 0.05) at the 6- and 12-month follow-up intervals (p = 0.007). There was a significant difference concerning the IKDC subjective score between the two study groups in favor of the combined ACL and ALL reconstruction group at 12 months postoperatively (p = 0.048). Combined ACL and ALL reconstruction technique was demonstrated to be effective in obtaining a superior control of the rotational knee instability and to improve the clinical objective and subjective outcomes when compared with isolated ACL reconstruction in sports patients with high-grade pivoting shifts.
Keywords: anterior cruciate ligament reconstruction; anterolateral ligament; lateral tenodesis; rotational stability; high-grade pivoting